2017
DOI: 10.1038/srep39938
|View full text |Cite
|
Sign up to set email alerts
|

Structural origin of fractional Stokes-Einstein relation in glass-forming liquids

Abstract: In many glass-forming liquids, fractional Stokes-Einstein relation (SER) is observed above the glass transition temperature. However, the origin of such phenomenon remains elusive. Using molecular dynamics simulations, we investigate the break- down of SER and the onset of fractional SER in a model of metallic glass-forming liquid. We find that SER breaks down when the size of the largest cluster consisting of trapped atoms starts to increase sharply at which the largest cluster spans half of the simulations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…This is reinforced further, by other studies showing that fractional SER in metallic glasses is coupled with the formation of large clusters of trapped atoms that percolate through the liquid. 84,85 Our results thus shed new light onto the structural properties of supercooled water, by means of a framework that steps away from the current paradigm of local order parameters to embrace the full complexity of the water network including the evolution of the empty space as well as topological properties of the HB network.…”
Section: Discussionmentioning
confidence: 84%
“…This is reinforced further, by other studies showing that fractional SER in metallic glasses is coupled with the formation of large clusters of trapped atoms that percolate through the liquid. 84,85 Our results thus shed new light onto the structural properties of supercooled water, by means of a framework that steps away from the current paradigm of local order parameters to embrace the full complexity of the water network including the evolution of the empty space as well as topological properties of the HB network.…”
Section: Discussionmentioning
confidence: 84%
“…* yylu@ciac.ac.cn † ljan@ciac.ac.cn ‡ zgw@caltech.edu Another anomalous behavior in the glass-forming liquids is the breakdown of the Stokes-Einstein (SE) relation, which relates the self-diffusion coefficient D to the viscosity or equivalently to the relaxation time τ α [9][10][11][12]. While for normal liquids the product Dτ α is temperature-independent, numerous studies [13][14][15][16][17][18][19] in recent decades have shown that this relation is violated in glass-forming liquids at low temperatures. Conceptually, Hodgdon and Stillinger [20,21] associated this violation with dynamic heterogeneity; however, there is considerable debate as to the mechanistic explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Evoy et al [296] find a best fit to their and literature data for C = 1.66 and t = 0.93. The SER is known to break down for glassy polymer systems in the limit of T g or high viscosity (e.g., [298,299]). When applied to atmospheric conditions in the planetary boundary layer and above, it is found that the diffusive mixing time based on the regular SER overestimates the result based on the fractional SER by a factor of three and higher in regions where mixing time is an hour or more.…”
Section: Organic Aerosol Diffusivity Modelsmentioning
confidence: 99%